Local Food at Italian Farmers’ Markets: Three Case Studies - Vecchio, Riccardo (The International Journal of Sociology of Agriculture and Food, 2010)
Despite the massive industrialization of the world agri-food system and the consequent detachment of food production from its consumption, several studies, conducted in Italy as well as in other European countries and in the United States, have shown growing consumer interest in recent years towards the local attribute of food. In this framework, farmers’ markets are perceived increasingly as key institutions in the trend towards a less industrialized agriculture and as vital developers of a strong link between urban consumers and rural food producers. Although a plethora of theoretical and empirical research on farmers’ markets can be retrieved in academic literature, important questions still remain concerning the demand and supply of locally produced goods at these forms of direct sale. The current article, presenting the results of consumers’ focus group discussions, in-depth interviews with vendors and direct observation at three Italian markets (Montevarchi, Naples and Potenza) provides empirical support that the desire to purchase locally produced food is not high on the list of surveyed shoppers’ priorities.